A conscious choice: Is it ethical to aim for unconsciousness at the end of life?. (17th December 2020) - Takla, Antony; Savulescu, Julian; Wilkinson, Dominic J. C.
Abstract: One of the most commonly referenced ethical principles when it comes to the management of dying patients is the doctrine of double effect (DDE). The DDE affirms that it is acceptable to cause side effects (e.g. respiratory depression) as a consequence of symptom‐focused treatment. Much discussion of the ethics of end of life care focuses on the question of whether actions (or omissions) would hasten (or cause) death, and whether that is permissible. However, there is a separate question about the permissibility of hastening or causing unconsciousness in dying patients. Some authors have argued that the DDE would not permit end of life care that directly aims to render the patient unconscious. The claim is that consciousness is an objective human good and therefore doctors should not intentionally (and permanently) suppress it. Three types of end of life care (EOLC) practices will be explored in this article. The first is symptom‐based management (e.g. analgesia); the second is proportional terminal sedation as a means of relieving suffering (also referred to as palliative sedation or continuous deep sedation); and finally, deliberate and rapid sedation to unconsciousness until death (a practice we call terminal anaesthesia in this paper). After examining the common arguments for the various types of symptom‐based management and sedation, we apply the DDE to the latter two types of EOLC practices. We argue that aiming at unconsciousness, contrary to some claims, can be morally good or at least morally neutral in some dying patients.